Innovation of Dental X-Ray Holder Using Silicone Rubber Coating in Posterior Dental Periapical Intraoral Examination - Marichatul Jannah; Saifudin, Saifudin; Gandhi, Wingghayarie Patra (JURNAL INFO KESEHATAN, 2021)
The major drawback of the parallel periapical examination technique is that the holder used can damage the oral tissues and cause discomfort to the patient. The objective of this study is to determine the work efficiency and radiographic quality of the innovative dental x-ray holder which has been made by adding synthetic rubber or silicone to the part of the holder that is in direct contact with the patient. This research is an experimental with a post-test only design. The analysis was performed based on filling out the questionnaire on a Likert scale ranging from 1 to 4. With the criteria 1. Disagree, 2. Sometimes, 3. Agree and 4. Strongly Agree. The test was administered by comparing the holder made with the commonly used Aphrodite holder as a control group. There were 16 repetitions of exposure to the cadaveric skull in obtaining research data for each treatment group. The results of statistical work efficiency testing on the control group resulted in a value of B = 0.125 with a significance of 0.071 and an effect of 10.5%. Meanwhile, for testing the quality of radiographic image, the value of B = 0.125 with a significance of 0.014 and an effect of 18.5% was obtained. The innovative dental x-ray holder using a silicone rubber layer is efficient and the resulting radiographic image quality is good when used in the intraoral examination.